Implikasi Disiplin Doa Dalam Membentuk Sikap Hati Jemaat Mengalami Pertumbuhan Iman di Gereja Zaitun Rasuli Indonesia (GZRI) Lubuk Pakam - Octavianus Nathanael; David Mariepan; Stasia Daeng Badjie; Imci Uli Marito Wate (Publikasi Kegiatan Pengabdian Masyarakat Widya, 2025)
This study discusses the implications of prayer discipline in shaping the congregation's heart attitude to experience faith growth at the Indonesian Apostles' Olive Church (GZRI) Lubuk Pakam. Christ has given parables about prayer and various teachings about it. Not only that, Christ also gives us an understanding of the guarantee of prayer and how important prayer is in increasing faith in God and growing into a transformed congregation so that it has a heart attitude, and in this case, is willing to be involved in existing services. Prayer is a form of communication with God conveyed in requests and requests to God, which can be in the form of hope, praise, and gratitude. This activity is a form of spirituality between humans and God where there is a relationship to build faith in God. This research is motivated by direct observation and involvement in activities called Community Service (PKM) at GZRI Lubuk Pakam, where it was found that there were attitudes of the heart that were still less aware of the importance of prayer. This attitude is influenced by the busy work activities of the congregation, resulting in a lack of response to every activity in the church, which in turn will hinder the growth of the congregation, not only in the quality of faith but also in the quantity of the congregation in the church. This study uses the methodfield research (field research) Data collected through observation, interviews, and documentation. The results showed a lack of response from the congregation. The responses analyzed reflected awareness, perseverance, and humility. The implications of these findings offer practical recommendations for service delivery at GZRI Lubuk Pakam. Keywords: Implications, Discipline of Prayer, Attitude of the Heart, Growth of Faith